THEORETICAL AND METHODOLOGICAL APPROACHES TO THE DEFINITION OF THE LAND MONITORING: Array - and; and (Municipal economy of cities. Series: «Economy science», 2018)
The purpose of the article is to substantiate the theoretical and methodological provisions for the definition of the concept of land monitoring, as well as the timely identification of changes, their assessment, prevention and elimination of the consequences of negative processes. Processing of information on the state of the city land Fund. Analysis of technical support of land monitoring. The land monitoring has subsystems, which correspond to the categories of land: monitoring of agricultural land; monitoring of residential and public lands; monitoring of lands of natural reserve and other purposes; monitoring of land for health purposes; monitoring land recreational recognition; monitoring of historical and cultural lands; forest land monitoring; monitoring of water Fund lands; monitoring of industrial land, transport, communications, energy, defense and other recognition; monitoring of land plots that are in stock. Thus, when monitoring urban land, each territorial unit is described by a group of factors. Each group contains a set of parameters, measured without delay or indirectly, with a ranked quantitative or qualitative characteristic. Assessments of territories, as a rule, are multi-purpose, therefore, it is hardly advisable to use integrated assessment for practical purposes. The diversity of requests of users of cadastral information implies, respectively, a variety of answers that allow to impose restrictions on the type of use of the territory, to make recommendations on the rationalization of the use of ground and underground space, the introduction of certain engineering improvements in the operating areas. Land monitoring is an integral part of environmental monitoring and is a system of monitoring the state of the land Fund of our country. Keywords: land monitoring, theoretical and methodological approaches the concept of land monitoring, planning, development of territories, development, urban factor.